Perancangan Bisnis Pembukaan Cabang Baru Pada CV. KMB Ditinjau Dari Aspek Pasar, Aspek Teknis, Dan Aspek Finansial - Fadila, Jeny Rachmad; Chumaidiyah, Endang; Pulungan, Muhammad Almaududi (Jayapangus Press, 2024)
KMB is a creative economy business that sells furniture equipment such as various kinds of ceramics, granite, sanitary and technical equipment in Pati Regency, Central Java. KMB (Kayani Maju Bersama) carries out marketing activities offline and online. The business has fluctuating income, does not have a clear upward or downward trend. This is caused by the lack of fulfillment of consumer demand due to the lack of storage and display space at business outlets. This research aims to determine whether or not it is feasible to plan to open a new KMB branch in an area with a wider market share. The method used in this research is quantitative descriptive and observation. The data collected is primary data in the form of market, technical and financial data obtained from the company. Furthermore, secondary data is obtained from internet sources or other literature studies. The results of designing market aspects obtained demand forecasting for the next five years with calculations using the SMA (Single Moving Average) method which includes potential markets, available markets and target markets. The results of the technical aspect design showed that the best new branch location was in Kudus Regency, the workforce was 29 people, and the total area of the new branch was 1350 m2. The results of the financial aspect design showed that the MARR was 15% with an NPV of IDR 8,110,680,197, an IRR value of 35.88%, and a PBP value of 3.65 years, which means that the three conditions were met for the business to be considered feasible. Apart from that, the sensitivity value is also taken into account by four important factors, namely an increase in product procurement costs with a sensitivity of 12.96%, a decrease in selling prices with a sensitivity of 30.61%, an increase in labor costs with a sensitivity of 197.12%, and a decrease in demand with a sensitivity of 9. .88%. Variables for each risk in market aspects, technical aspects and financial aspects owned by KMB are also measured by the NPV results of IDR 2,870,193,102, IRR value of 35.88%, and PBP value of 4.98 years, which means it can still be said to be feasible.